UNVEILING MATH MASTERY: CRAFTING DYNAMIC LEARNING TOOLS TO ELEVATE PROBLEM-SOLVING PROFICIENCY - Epa Wira Suparman (The American Journal of Social Science and Education Innovations, 2024)
In the realm of mathematics education, the quest for effective strategies to enhance problem-solving proficiency is perpetual. This study explores the design and implementation of learning media grounded in discovery learning principles, aiming to unravel its impact on students' problem-solving abilities. The research delves into the intricacies of crafting dynamic learning tools that promote active engagement, critical thinking, and a deeper understanding of mathematical concepts. Through a meticulously structured approach, this study seeks to shed light on the transformative potential of innovative learning media in empowering students to unveil and master the art of problem-solving in mathematics.